ChemInform Abstract: Asymmetric Synthesis of Spiropyrazolones by Sequential Organo‐ and Silver Catalysis. Issue 22 (12th May 2016) - Hack, Daniel; Duerr, Alexander B.; Deckers, Kristina; Chauhan, Pankaj; Seling, Nico; Ruebenach, Lukas; Mertens, Lucas; Raabe, Gerhard; Schoenebeck, Franziska; Enders, Dieter
Abstract: An asymmetric Michael addition and a formal Conia‐ene reaction give rise to a stereoselective one‐pot synthesis of spiropyrazolones.